2015
DOI: 10.1073/pnas.1503381112
|View full text |Cite
|
Sign up to set email alerts
|

Fat, weather, and date affect migratory songbirds’ departure decisions, routes, and time it takes to cross the Gulf of Mexico

Abstract: Approximately two thirds of migratory songbirds in eastern North America negotiate the Gulf of Mexico (GOM), where inclement weather coupled with no refueling or resting opportunities can be lethal. However, decisions made when navigating such features and their consequences remain largely unknown due to technological limitations of tracking small animals over large areas. We used automated radio telemetry to track three songbird species (Red-eyed Vireo, Swainson's Thrush, Wood Thrush) from coastal Alabama to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
218
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(224 citation statements)
references
References 75 publications
(97 reference statements)
6
218
0
Order By: Relevance
“…This wealth of data has led to comprehensive and diverse applications in the study of breeding and postbreeding dispersal, stopover and migration behavior, and overwintering ecology. For example, detection data from Motus collaborators have been used to estimate stopover duration (Dossman et al 2016, Mann et al 2017, Neima 2017, activity level, e.g., onset of diel activity, stopover versus active migration (Crysler et al 2016;Morbey et al, unpublished data), regional and site fidelity during migratory stopover (Mann et al 2017, Neima 2017, precise departure and arrival times , Dossman et al 2016, Müller et al 2016), departure and flight orientation , Crysler et al 2016, Kishkinev et al 2016, Neima 2017, flight distance, time, and therefore flight speed (Woodworth et al 2014, 2015, Brown and Taylor 2015, Crysler et al 2016, Falconer et al 2016, colony attendance patterns (Loring 2016), and types of movements, e.g., migratory, relocation (Woodworth et al 2014, 2015, Crysler et al 2016). …”
Section: Current Usesmentioning
confidence: 99%
“…This wealth of data has led to comprehensive and diverse applications in the study of breeding and postbreeding dispersal, stopover and migration behavior, and overwintering ecology. For example, detection data from Motus collaborators have been used to estimate stopover duration (Dossman et al 2016, Mann et al 2017, Neima 2017, activity level, e.g., onset of diel activity, stopover versus active migration (Crysler et al 2016;Morbey et al, unpublished data), regional and site fidelity during migratory stopover (Mann et al 2017, Neima 2017, precise departure and arrival times , Dossman et al 2016, Müller et al 2016), departure and flight orientation , Crysler et al 2016, Kishkinev et al 2016, Neima 2017, flight distance, time, and therefore flight speed (Woodworth et al 2014, 2015, Brown and Taylor 2015, Crysler et al 2016, Falconer et al 2016, colony attendance patterns (Loring 2016), and types of movements, e.g., migratory, relocation (Woodworth et al 2014, 2015, Crysler et al 2016). …”
Section: Current Usesmentioning
confidence: 99%
“…Although geolocators have revealed prolonged stops for multiple songbird species, understanding of stopover and movement behavior in these staging areas is still limited, since the coarse latitudinal precision of geolocators (~300 km) precludes study of fine-scale behavior (McKinnon et al 2014, Deppe et al 2015. Even relatively large landscape-scale stopover movements recorded with automated telemetry (e.g., 250 km; Brown and Taylor 2017) would not be registered with geolocators.…”
Section: Introductionmentioning
confidence: 99%
“…During fall migration, vireos are regularly sited along most of the eastern U.S. coastline (Sullivan et al 2009). They reach the breeding grounds by either crossing or circumnavigating the Gulf of Mexico (Deppe et al 2015) and thus represent a short-jump migrant. By contrast, most blackpolls exhibit an extreme jump strategy that involves a 2,500 km transatlantic flight from the eastern coast of the U.S. (DeLuca et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the final decision to resume migration depends on the interplay between environmental conditions, the endogenous program, and the physiological condition of an individual. Theory predicts that stopover decisions depend on amount and rate of deposition of energy stores (1,2), and empirical findings have confirmed this hypothesis (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The big and yet unanswered question is, How do birds know that they are ready to depart?…”
mentioning
confidence: 99%
“…Previous work has shown that fat stores are the best predictor for migratory disposition and stopover duration: Birds with larger subcutaneous (s.c.) fat stores show more migratory restlessness in captivity (8,10,13,14), stay shorter times at stopover sites (9,11), and migrate faster (12). Because birds fuel their migratory flights primarily through fatty acid metabolism (15)(16)(17), we expect that factors reflecting fuel load or the energetic condition must be involved in the behavioral switch between resting at stopover sites and resuming migration.…”
mentioning
confidence: 99%